A) 5x + 5y – 4z = 13
B) 5x + 3y + z = –3
C) 3x – 2y – z = –10
Adding B) and C) we get equation D
D) 8x + y = -13
Multiplying equation B by 4 we get:
20x + 12y +4 = -12 then adding this to A)
5 x + 5y -4z = 13 we get equation E:
E) 25x + 17y = 1 multiplying equation D by -17 we get
D) -136x -17y = 221 Then we add E and D and get
-111x = 222
x = -2
Putting x = -2 into equation D)
D) 8x + y = -13
D) -16 +y = -13
y = 3
FINALLY we put
x = -2 and y = 3 into equation A)
A) 5*-2 + 5*3 – 4z = 13
A) -10 + 15 -4z = 13
A) -4z = 8
z = -2
Yes, it's just that simple. LOL !!!!!